Potential productivity of crosses of varieties of open pollination with simple hybrids of corn. - Espinosa, Alejandro (2016)
Given the acceplance, in the high valleys of Mexico -2200 to 2600 mts. over sea level-, of free-pollination strains and the high productivity of hybrids, we considered the alternative of combining these frec-pollination strains with the H-34, thus obtaining another experi-mental single hybrid and our goal was to determine its potential productivity level. The strains known aas Ixtlahuaca, Santiago Yeche and Acambay improved from 37,3% to 20,8% their productivity when crossed with H-34, such was not the case with the strains Almoloya de Juarez and V-23. The other single hybrid was named 417, and it led to aHigher productivity in Ixtlahuaca with 29.1%. When we conbined H-33 x 417 it yielded 9728 kglha, a 7% higher than that of 9088kg/ha with H-33. The results of VS-22x 417 were very similartothose with VS-22. The results indicated that we could use H-34 and perhaps other single hybrids in combination with free-pollina-tion strains, thus obtaining a certain level of heterosis and facilitating seed production, but based on the different responses, this should beevaluated previous to any combination be performed.